Questions of constructing probe active control devices for product sizes - E. V. Leun (Омский научный вестник)
The article presents probe active control devices (ACD) of the size of products, describes the composition, versions, principle and modes of operation. The measurements are carried out by two-coordinate vibration oscillations of the tip along a closed path with a section of co-directional motion and mechanical contact of the lс with the surface of the moving product. The tip moves vtip with a slight lag from products vdet with a small relative velocity , thus implementing a moving feeling, like a needle profilometer or a cantilever, measuring its position in two coordinates lx and ly. The measurements consist of a sequence of such feelings. The article discusses the issues of the functionality, continuity and accuracy of probe ACD measurements.